A Collagenolytic Aspartic Protease from Thermomucor indicae-seudaticae Expressed in Escherichia coli and Pichia pastoris - Pereira, Waldir Eduardo Simioni [UNESP]; da Silva, Ronivaldo Rodrigues [UNESP]; de Amo, Gabriela Salvador; Ruller, Roberto; Kishi, Luciano Takeshi; Boscolo, Maurício [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Springer Nature, 2020)
Proteases are produced by the most diverse microorganisms and have a wide spectrum of applications. However, the use of wild microorganisms, mainly fungi, for enzyme production has some drawbacks. They are subject to physiological instability due to metabolic adaptations, causing complications and impairments in the production process. Thus, the objective of this work was to promote the heterologous expression of a collagenolytic aspartic protease (ProTiN31) from Thermomucor indicae seudaticae in Escherichia coli and Pichia pastoris. The pET_28a (+) and pPICZαA vectors were synthesized containing the gene of the enzyme and transformed into E. coli and P. pastoris, respectively. The recombinant enzymes produced by E. coli and P. pastoris showed maximum activity at pH 5.0 and 50 °C, and pH 5.0 and 60 °C, respectively. The enzyme produced by P. pastoris showed better thermostability when compared to that produced by E. coli. Both enzymes were stable at pH 6.0 and 6.5 for 24 h at 4 °C, and sensitive to pepstatin A, β-mercaptoethanol, and Hg2+. Comparing the commercial collagen hydrolysate (Artrogen duo/Brazil) and gelatin degradation using protease from P. pastoris, they showed similar peptide profiles. There are its potential applications in a wide array of industrial sectors that use collagenolytic enzymes.
Keywords: Aspartic protease; Collagenase; Peptidase; Proteolytic enzyme; Thermomucor indicae-seudaticae